Mutation analysis of sporadic early-onset Alzheimer's disease using the NeuroX array - Barber, Imelda S.; Braae, Anne; Clement, Naomi; Patel, Tulsi; Guetta-Baranes, Tamar; Brookes, Keeley; Medway, Christopher; Chappell, Sally; Guerreiro, Rita; Bras, Jose; Hernandez, Dena; Singleton, Andrew; et al. (Elsevier, 2017)
We have screened sporadic early-onset Alzheimer’s disease (sEOAD, n=408) samples using the NeuroX array for known causative and predicted pathogenic variants in 16 genes linked to familial forms of neurodegeneration. We found two sEOAD individuals harbouring a known causative variant in PARK2 known to cause early-onset Parkinson’s disease (EOPD); p.T240M (n=1) and p.Q34fs delAG (n=1). Additionally, we identified three sEOAD individuals harbouring a predicted pathogenic variant in MAPT (p.A469T) which has previously been associated with AD. It is currently unknown if these variants affect susceptibility to sEOAD, further studies would be needed to establish this. This work highlights the need to screen sEOAD individuals for variants that are more classically attributed to other forms of neurodegeneration.